Hubungan Antara Quality of Life dan Motivasi Belajar Siswa SMA/Sederajat di Jakarta Selama Masa Pandemi Covid-19 - Alma Tiarani; Margaretha Purwanti; Aireen Rhammy Kinara Aisyah (MANASA, 2021)
This study aimed to see the relationships between quality of life and learning motivation of high school students in Jakarta during the Covid-19 pandemic. The pandemic had a significant impact on society in Indonesia, including middle adolescence who are generally high school students. During the pandemic, several rules were put in place to break the chain of transmission of the coronavirus. Conditions that tend to be difficult to predict and dynamic during a pandemic were suspected to affect the quality of life and individual learning motivation. This study uses a quantitative approach with a questionnaire as a data collection tool. The questionnaires used were the World Health Organization Quality of Life – BREF (WHOQOL-BREF) and the Motivated Strategies for Learning Questionnaire (MSLQ). Analysis of relationships between quality of life (QoL) and learning motivation by testing the correlation between aspects and components in the two variables. Participants in this study were high school students, currently undergoing PJJ, and domiciled in Jakarta. The participants used in the data analysis process were 168 people. The results showed that there was a positive relationship between aspects of quality of life and components of learning motivation (rs = 0.189 – 0.363, p < .05, two-tailed). However, there is no relationship between aspects of quality of life and one component of learning motivation, namely the affective component (rs = -0.069 – 0.133, p > .05, two-tailed). The relationship between quality of life and learning motivation shows the significant role of the environment. It is expected that high school students, parents, teachers, and schools always establish communication and work together so that students have a quality of life and optimal learning motivation during the pandemic.